Knowledge about glaucoma among patients attending the outpatient department of the department of ophthalmology of a tertiary care hospital - Raina, Bhavani; Mahajan, Sachit (International Journal of Research in Medical Sciences, 2022)
Background: Glaucoma is the leading cause of irreversible blindness in the world. It is a noncommunicable chronic eye disease which needs lifelong care and treatment. Optic nerve damage is progressive and the disease mostly remains asymptomatic which makes it a public health challenge. Raising public awareness and knowledge about glaucoma is a key factor in early detection and management. The aim of the study was to assess knowledge about glaucoma among patients attending the eye outpatient department (OPD) of a tertiary care hospital. Methods: This study was conducted on 100 patients who attended the eye OPD of department of ophthalmology, Government Medical College (GMC), Jammu from December 2021 to May 2022. The study subjects were given a questionnaire and they had to respond to questions by choosing one of the three options. Results: In our study the mean age of patients was 50.65 years with majority of patients (50%) falling in the age group of 30 to 50 years. The male to female ratio was 1.7:1. Only 23% of the study subjects were knowledgeable about the fact that glaucoma was the most important cause of irreversible blindness. 83% of the respondents correctly identified people over 40 years of age at risk for developing glaucoma. Only 25% of the respondents identified pressure related damage to optic nerve as a feature of glaucoma. Majority of patients were unaware about asymptomatic nature of glaucoma. 93% of the study subjects considered glaucoma treatable. Only 23% had knowledge that irreversible loss of vision was the end result of glaucoma. Conclusions: This study showed that knowledge about glaucoma was limited in our part of the country. There is a need to increase awareness about the disease so that we can reduce the burden of glaucoma related blindness.